Electricity supply in Germany can be secured without Russian supplies and nuclear energy: The 2030 coal-phase out remains possible - Christian Hauenstein; Karlo Hainsch; Philipp Herpich; Christian R. von Hirschhausen; Franziska Holz; Claudia Kemfert; Mario Kendziorski; Pao-Yu Oei; Catharina Rieve (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
The European Union has increased pressure on Russia by enacting a coal embargo. Following a transition period, Russian coal imports will end in August 2022. Recent studies show that Germany will be able to substitute Russian supplies with imports from other countries by summer 2022. However, with the looming threat of a Russian gas supply stop, plans must be developed to ensure security of supply. In scenario calculations, DIW Berlin analyzed how the German electricity system can respond to a stop of Russian energy supplies (especially coal and natural gas) while still maintaining the accelerated coal phase-out and the 2022 nuclear phase-out plans. The calculations show that a secure electricity supply will be possible in 2023, even without Russian energy supplies. The shutdown of the final three nuclear power plants can and should take place as planned in December 2022. In the short term, coal-fired power plants from the grid reserves will have to be used and the standby mode of some power plants will have to be extended. In the medium term, the accelerated expansion of renewable energy infrastructure as envisaged by the German government in the set of measures known as the Easter Package is expected to lead to a decline in demand for natural gas and coal-fired power generation by 2030. Thus, an accelerated coal phase-out by 2030 as laid out in the coalition agreement is still possible.
Keywords: 330